Foundations of software and system performance engineering : process, performance modeling, requirements, testing, scalability, and practice - Bondi, Andre B. (Upper Saddle River, New Jersey : Pearson Education, 2015)
This book provides techniques and skills necessary to implement performance engineering at the beginning of a project and manage it throughout the product$1 (Bs life cycle.s
1. Why performance engineering? Why performance engineers? -- 2. Performance metrics -- 3. Basic performance analysis -- 4. Workload identification and characterization -- 5. rom workloads to business aspects of performance requirements -- 6. Qualitative and quantitative types of performance requirements -- 7. Eliciting, writing, and managing performance requirements -- 8. System measurement techniques and instrumentation -- 9. Performance testing -- 10. System understanding, model choice, and validation -- 11. Scalability and performance -- 12. Performance engineering pitfalls -- 13. Agile processes and performance engineering -- 14. Working with stakeholders to learn, influence, and tell the performance engineering story -- 15. Where to learn more.
Includes bibliographical references and index.
Keywords: SYSTEMS ENGINEERING